Suctioning Versus Traditional Access Sheath in Mini-Percutaneous Nephrolithotomy: A Systematic Review and Meta-analysis - chen, Di; chen, Changsheng; Xie, Yurun; Luo, Zhihua; Liu, Gang (Urology Journal, 2021)
Purpose: The suctioning access sheath (SAS) is a novel access sheath connected to a negative pressure suction device and absorbs fragments. Some comparative studies have reported SAS with a higher stone-free rate and lower operative time. However, no higher-level evidence was published to support SAS. Hence, this systematic review and meta-analysis aimed to assess the clinical safety and efficacy of SAS versus traditional access sheath (TAS) for the treatment of renal stones in mini-percutaneous nephrolithotomy (MPCNL). Materials and Methods: A systematic review of the literature was conducted using Pubmed, Embase(Ovid), Medline（EBSCO）, Cochrane central register of controlled trials, and Sinomed to search comparative studies as recent as December 2020 that assessed the safety and effectiveness of SAS in PCNL. The quality of retrospective case-control studies (RCCs) and randomized controlled trials (RCTs) were evaluated by the Newcastle-Ottawa Scale (NOS) and the Cochrane risk of bias tool, respectively. The Oxford center set up evidence-based medicine was used to assess the level of evidence (LE). Statistical analyses were performed by the comprehensive meta-analysis program. Results: Seven studies, with a total of 1655 patients, were included. Compared with the TAS group, the SAS group had a shorter operative time (MD= -17.30; 95%CI:-23.09,-11.51; P＜.00001), higher stone-free rate (OR=2.37;95%CI:1.56,3.61;P<.0001), fewer total complication rate (OR=0.50;95%CI:0.35,0.70;P<.0001), lower auxiliary procedures rate (OR=0.48;95%CI:0.36,0.64; P<.00001), and lower postoperative fever rate (OR=0.46;95%CI:0.34,0.62;P＜.00001). Conclusion: The SAS can significantly improve MPCNL in the stone-free rate, operative time, and total complication rate, especially for auxiliary procedures and postoperative fever rates.